(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Important moral and philosophical framework of the English literature and some important twentieth-century English writers and their ideas from Islamic perspectives have been assessed. Such an approach to English literature is vital for establishing its relevance to Muslim societies and is in line with postcolonial perspectives on the subject. It is intended to suggest an alternative (Islamic) way of looking at English writers and their works, especially considering the cultural realities of Muslim settings.